IMPLEMENTASI METODE WATERFALL PADA PERANCANGAN SISTEM INFORMASI PELAYANAN RAWAT JALAN PUSKESMAS TELAGASARI KARAWANG - Tabrani, Muhamad (Indonesian Journal of Business Intelligence (IJUBI), 2019)
In the current era of globalization, information technology is advancing rapidly. Every government and self-government institution is even required to be able to present information quickly and accurately in the world of work. In this case the computer has an important role for everyone, because computers are one of the fastest media to facilitate the presentation of information quickly and accurately. In the world of work such as health services in health centers whose activities are still carried out manually and have not been maximally computerized, so that it will cause several problems that can reduce the performance of services to the community, such as a long service time. For this reason the author makes a website Designing a Web-Based Outpatient Information System at the Telagasari Health Center in Karawang to support services and provide better services in the future. With the help of a computer that has a data storage system that is supported by security, it is expected that service and reporting activities can run effectively and also to minimize the error or loss of data carried out by service officers in the puskesmas so as to produce a fairly good program.